Menstrual irregularity and its associated factors among college students in Ethiopia, 2021 - Mittiku, Yohannes Moges; Mekonen, Haile; Wogie, Girma; Tizazu, Michael Amera; Wake, Getu Engida (Frontiers in Global Women's Health, 2022)
Background: Menstrual cycle is a normal physiological process that is characterized by periodic and cyclic shedding of progestational endometrium, which is a result of a coordinated sequence of events involving the hypothalamus, anterior pituitary, ovaries, and endometrium. Menstrual irregularities are common gynecological problems in reproductive women and have impacts on the economic, social, and health of the women. Objective: The objective of this study was aimed to assess the Magnitude of Menstrual Cycle Irregularity and Associated Factors among College students in Debre Berhan Town, North Shewa, Amhara, Regional State, Ethiopia, 2021 Methods: Institution-based cross-sectional study was conducted from June to July 2021 in Debre Berhan town. Data was collected using self-administer questionnaires in 420 eligible female college students by systematic random sampling technique and weight and height were measured then Body Mass Index(BMI) was calculated after data collection. Each questionnaire was checked for completeness, cleaned, coded, and entered into EPI-DATA then transported to SPSS software. Bivariate and multivariate logistic regression analyses were employed to determine the association of each independent variable with the dependent variable. P-value ≤ 0.05 were used to declare association and select predictors Results: In the current study, 395 students participated with a response rate of 93.6%. Of all the total respondents, the magnitude of menstrual cycle irregularity was 33.4% (95% CI 28.6–38.2). Age less than 20 years old [AOR=3.88, 95% CI (1.25-12.18)], age of menarche <=12 years [AOR= 4, 95% CI (1.18-13.9), sleeping hours<= 5hr [AOR= 2.26, 95% CI (1.04-4.93)], Had Psychological stress [AOR=2, 95% CI (1.53-3.23)] and overweight [AOR= 2, 95% CI(1.13- 3.23) were the variables significantly associated with the magnitude of menstrual irregularity. Conclusion and recommendation In this study, more than one-third of the college students in Debre Berhan town have experienced menstrual irregularity. Being less than 20 years old, having a history of early menarche, being overweight, and having psychological stress were a variable significantly associated with menstrual irregularity. To improve menstrual irregularities, girls should control their weight and lead a healthy lifestyle, including adequate sleep.